Magnetic resonance imaging and clinical outcome in patients with symptomatic carotid artery stenosis after carotid artery revascularization - Badacz, Rafał; Kabłak-Ziembicka, Anna; Urbańczyk-Zawadzka, Małgorzata; Banyś, Robert P.; Musiałek, Piotr; Odrowąż-Pieniążek, Piotr; Trystuła, Mariusz; Ścigalski, Jan; Żmudka, Krzysztof; Przewłocki, Tadeusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: About 30% of patients with carotid artery stenosis (CAS) develop dementia after a cerebral ischemic event (CIE), and 20–50% suffer from CIE recurrence during 6 months. Carotid artery revascularization (CAR) may prevent CIE recurrence, at the cost of new microembolic lesions (MES). The impact of CAR on cognitive function is debatable. Aim : To assess functional and cognitive outcome, cerebral flow on transcranial Doppler (TCD) and brain magnetic resonance imaging (MRI) in patients with symptomatic CAS referred for CAR. Material and methods : Twenty-two patients (aged 69.0 ±7.2 y.o., 15 male) with recent CIE (21.9 ±20.9 days to CAR) related to CAS of mean 89.8 ±3.9% lumen reduction were prospectively evaluated with TCD, diffusion and perfusion MRI, Montreal Cognitive Assessment (MoCA), Mini Mental State Examination (MMSE), modified Rankin Scale (mRS) and the National Institutes of Health Stroke Scale (NIHSS) 24 h before, at 24–48 h and 1 month following CAR. Results : New MES were found in 11 (50%) subjects following CAR. CAR resulted in a significant increase of cerebral flow velocity in the middle and anterior cerebral arteries (p < 0.002 and p = 0.003; respectively) and cerebral perfusion measured by time to peak (TTP) and mean transit time (MTT) (p = 0.0009 and p = 0.0002; respectively). Neurologic tests showed improvement in NIHSS (2.4 ±1.6 to 1.5 ±1.2, p = 0.003), mRS (from 1.3 ±0.9 to 0.7 ±0.9, p = 0.005), and MMSE (26.7 ±2.2 to 27.6 ±2.3, p = 0.019) at 1 month, while similar MoCA scores were observed before and 1 month after CAR (23.4 ±3.3 vs. 24.1 ±3.7, p = 0.136). Conclusions : Improvement of cerebral flow and perfusion and functional outcome, as well as at least no cognitive decline, is observed after CAR for symptomatic CAS.